ANALYSIS OF FACTORS AFFECTING INTEREST IN BUYING A HOUSE - Saut Maruli Tua Pandiangan (Journal of Innovation Research and Knowledge, 2022)
The purpose of this study is to analyze factors affecting interest in buying a house, case study D'Green Town House Housing. This type of research uses quantitative research. The population in this study are 15 houses of residents of D'Green Town House Housing. Samples are taken using saturated sampling. So the sample in this study is 15 houses of residents of D'Green Town House Housing. The method of analysis in the research is partial test (t) results. The research results show that location factor has a significant effect on interest in buying a house, case study D'Green Town House Housing. Environmental factor has a significant effect on interest in buying a house, case study D'Green Town House Housing.